Lignin‐First Monomers to Catechol: Rational Cleavage of C−O and C−C Bonds over Zeolites. Issue 7 (27th January 2022) - Wu, Xian; Liao, Yuhe; Bomon, Jeroen; Tian, Guilong; Bai, Shao‐Tao; Van Aelst, Korneel; Zhang, Qiang; Vermandel, Walter; Wambacq, Ben; Maes, Bert U. W.; Yu, Jihong; Sels, Bert F.
Abstract: A catalytic route is developed to synthesize bio‐renewable catechol from softwood‐derived lignin‐first monomers. This process concept consists of two steps: 1) O ‐demethylation of 4‐ n ‐propylguaiacol (4‐PG) over acidic beta zeolites in hot pressurized liquid water delivering 4‐ n ‐propylcatechol (4‐PC); 2) gas‐phase C ‐dealkylation of 4‐PC providing catechol and propylene over acidic ZSM‐5 zeolites in the presence of water. With large pore sized beta‐19 zeolite as catalyst, 4‐PC is formed with more than 93 % selectivity at nearly full conversion of 4‐PG. The acid‐catalyzed C ‐dealkylation over ZSM‐5 zeolite with medium pore size gives a catechol yield of 75 %. Overall, around 70 % catechol yield is obtained from pure 4‐PG, or 56 % when starting from crude 4‐PG monomers obtained from softwood by lignin‐first RCF biorefinery. The selective cleavage of functional groups from biobased platform molecules through a green and sustainable process highlights the potential to shift feedstock from fossil oil to biomass, providing drop ins for the chemicals industry. Abstract : Pining for catechol : A catalytic route is developed to synthesize bio‐renewable catechol from pinewood‐derived lignin‐first monomers. The two‐step process consists of O ‐demethylation of 4‐ n ‐propylguaiacol over acidic beta zeolites in hot pressurized liquid water, delivering 4‐ n ‐propylcatechol, and gas‐phase C ‐dealkylation of 4‐propylcatechol providing catechol and propylene over acidic ZSM‐5 zeolites in the presence of water.